2018
DOI: 10.4172/2167-7921.1000262
|View full text |Cite
|
Sign up to set email alerts
|

Modern Non-Pharmacological and Non-Surgical Treatments for Hip Pain

Abstract: Osteoarthritis of the hip describes a clinical syndrome of joint pain accompanied by varying degrees of functional limitation and reduced quality of life. Osteoarthritis may not be progressive and most patients will not need surgery, with their symptoms adequately controlled by non-surgical measures. The treatment of hip osteoarthritis is aimed at reducing pain and stiffness and improving joint mobility. Total hip replacement remains the most effective treatment option but it is a major surgery with potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
1
1
0
Order By: Relevance
“…These findings align well with previous research (35) advocating a relatively higher efficacy of hip OA joint surgery. Only 2 studies (both based on the EQ-5D) investigated HSUVs in hip OA core intervention patients, which aligned well with the previous findings of the dearth of studies measuring the HSUVs in patients using hip OA core interventions (36,37). No studies on hip OA medication and injection treatments were identified in our review as expected (38,39), hence, no meta-analysis for these treatments was possible.…”
Section: Discussionsupporting
confidence: 81%
“…These findings align well with previous research (35) advocating a relatively higher efficacy of hip OA joint surgery. Only 2 studies (both based on the EQ-5D) investigated HSUVs in hip OA core intervention patients, which aligned well with the previous findings of the dearth of studies measuring the HSUVs in patients using hip OA core interventions (36,37). No studies on hip OA medication and injection treatments were identified in our review as expected (38,39), hence, no meta-analysis for these treatments was possible.…”
Section: Discussionsupporting
confidence: 81%
“…The hip disorders include congenital disorders, degenerative disease, avascular necrosis and fracture, which are the main causes to lead to total hip arthroplasty [ 3 , 4 , 5 , 6 ]. Non-surgical treatments are available to reduce pain and improve hip mobility [ 7 , 8 ]. However, if non-surgical treatments fail to provide relief, total hip replacement (THR) may be recommended.…”
Section: Introductionmentioning
confidence: 99%